Pengaruh Permainan Mufradat Musalsalah (Sambung Kata ) Terhadap Peningkatan Maharah Kalam Siswa Kelas VIII Mts Mambaul Ulum Dagan Solokuro Lamongan Tahun Pelajaran 2023/2024 - Muzlifatul Jannah; Nurul Fahmi (Ta'lim : Jurnal Multidisiplin Ilmu, 2024)
The Arabic language learning procces at MTs Mambaul Ulum Dagan is less attractive to students because it tends to be monotonusand saturated. The problem that often arises is that students still find it difficuly to understand Arabic language learning, especially in maharah kalam. Therefore, researchers are interested in implementing learning with the mufradat musalsalah (word connection) game, a game which has never been applied in Arabic language learning at MTs Mambaul Ulum Dagan. The type of research used is experimental research with a quantitative approach. The population is class VIII students of MTs Mambaul Ulum Dagan and the sample is a saturated sample where the entire population is part of a sample of 34 students. The instruments used are observation, tests, documentation, interviews, and questionaires. The result of this research, based on calculations using T-tes formula, the result is -7,823 and d.b namely N-1=34-1=33. Meanwhile the T-tes table use one group refering to significant number level of 0,05 namely 1,397 and 0,01 which is 2,457. So the conclusion is that the T-test is smaller than the significant value level of the table so that ho is rejected and ha is accepted due to the significant positive influence of the implementation of the mufradat musalsalah ( word connection) game on increasing the maharah kalam of class VIII MTs Mambaul Ulum Dagan Solokuro Lamongan Academic year 2023/2024